2021
DOI: 10.1021/acs.jpcc.0c10935
|View full text |Cite
|
Sign up to set email alerts
|

From Aluminum Foil to Two-Dimensional Nanocrystals Using Ultrasonic Exfoliation

Abstract: Al nanostructures have unique optical properties such as widely tunable surface plasmon resonances from deep UV to NIR that can be used for label-free fluorescence enhancement and surface-enhanced Raman scattering. Various Al nanostructures have been fabricated using sophisticated "top-down" lithographic and "bottom-up" colloidal methods. Here, we developed a simple and efficient method of synthesizing two-dimensional (2D) aluminum (Al) nanocrystals from commercially available Al foil using ultrasonic exfoliat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…14 However, the presence of byproducts in the solution was hindering the usefulness of the method. Note that very recently, a related approach was reported by Lu et al, 11 who demonstrated the creation of crystalline 2D nanocrystals (flakes) after ultrasonic exfoliation of commercial Al foils. The method remains limited to the synthesis of 2D nanoparticles and their size is not under control.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…14 However, the presence of byproducts in the solution was hindering the usefulness of the method. Note that very recently, a related approach was reported by Lu et al, 11 who demonstrated the creation of crystalline 2D nanocrystals (flakes) after ultrasonic exfoliation of commercial Al foils. The method remains limited to the synthesis of 2D nanoparticles and their size is not under control.…”
Section: Introductionmentioning
confidence: 94%
“…While the chemical synthesis of gold and silver nanoparticles is common knowledge, the synthesis of Al nanoparticles is not so easy, with only a handful of reports published so far. [8][9][10][11] The underlying reason is the fact that the method used for noble metals, the reduction of a metallic salt, cannot be directly translated to aluminum because the classical reducers cannot reduce aluminum salt. Hence, other approaches are required.…”
Section: Introductionmentioning
confidence: 99%
“…37 Lu et al ultrasonically exfoliated small pieces of aluminum foil into 2D aluminum sheets of approximately 1 mm in ethylene glycol. 90 Yadav et al employed an easily scalable technique to synthesize 2D metal alloys from 3D quasicrystal precursors. 91 They extracted the corresponding 2D structures of decagonal quasicrystals (QCs) from the bulk Al 66 Co 17 Cu 17 alloy via high-strength exfoliation in a pressurized ultrasonic reactor.…”
Section: Synthesis Strategies Of Metallenesmentioning
confidence: 99%
“…However, the presence of byproducts in the solution was hindering the usefulness of the method. Note that very recently, a related approach was reported by Lu et al, who demonstrated the creation of crystalline 2D nanocrystals (flakes) after ultrasonic exfoliation of commercial Al foils. The method remains limited to the synthesis of 2D nanoparticles and their size is not under control.…”
mentioning
confidence: 96%
“…Furthermore, chemical approaches generally yields crystalline and shape-controlled nanoparticles, giving better quality (i.e., higher quality factor) plasmonic resonances. While the chemical synthesis of gold and silver nanoparticles is common knowledge, the synthesis of Al nanoparticles is not so easy, with only a handful of reports published so far. The underlying reason is the fact that the method used for noble metals, the reduction of a metallic salt, cannot be directly translated to aluminum because the classical reducers cannot reduce aluminum salt. Hence, other approaches are required.…”
mentioning
confidence: 99%